MODEL HUBUNGAN ANTARA KONDISI FUNGSIONAL DAN KONDISI STRUKTURAL SEBAGAI ESTIMASI KONDISI PERKERASAN PADA JALAN NASIONAL DI SULAWESI SELATAN DAN KALIMANTAN SELATAN - Androsario Sarimuda Wasta; Miftahul Fauziah; Subarkah Subarkah (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2019)
Evaluation of correlations regression between functional condition roads and structural condition of the pavement needs to be implemented, a result of condition handling the maintenance of roads in the province of South Sulawesi and South Kalimantan are still less accurate because the determination of handling is only determined from one of the condition steadiness of road, Data used to facilitate this research is secondary to data obtained in 2014, in which secondary data obtained from Balai Besar Pelaksanaan Jalan Nasional (BBPJN) and Balai Pelaksanaan Jalan Nasional (BPJN). Flexible pavement conditions on the roads of research in South Kalimantan Province, shows the surface roughness (IRI) has a the level of correlation conditions that reasonably represen the elastic modulus of surface layer (E1), but the surface roughness (IRI) has a level of correlation that less represents the elastic modulus of base layer (E2 ), while a different result is also shown by the surface roughness (IRI) can not represent the elastic modulus of subbase layer (E3) and the elastic modulus of subgrade layer (E4). While the condition of pavement flexible on the roads of research in South Sulawesi province, shows the surface roughness (IRI) has a level of correlation conditions that already represents the elastic modulus of surface layer (E1), but the surface roughness (IRI) has a level of correlation that reasonably represents the elastic modulus of base layer ( E2), while a different result is also shown by the surface roughness (IRI) is less representative of the elastic modulus of subbase layer (E3) and the elastic modulus of subgrade layer (E4). The difference correlation of regression relationship model’s between the functional conditions and the structural conditions for all the roads, indicated the influence of the type of pavement layers and pavement layer thickness all layer of of pavement for all the roads.